(untitled) (Bangladesh Journal of Animal Science, 2014)
A total of 48 Shaver-579 chicken layers aged between 85 to 94 weeks were reared in individual cages and given a basal diet amounting to 115g feed/bird/day. The basal diet fortified with 0.05, 0.10 or 0.15% Rena-Phytase-400 constituted of 3 experimental diets to see the effects of exogenous phytase on egg production and egg quality. Results indicated that increasing level of exogenous phytase in diet almost linearly (p<0.05) increased egg production and feed conversion but did not affect egg quality. Providing phytase in the diet at 0.05, 0.10 and 0.15% increased egg production by 11.86, 22.2 and 24.58%, respectively. It was shown that highest egg production was found at 0.15% phytase levels in diet. It can be concluded that egg production of aged hen could be increased by adding said amount of exogenous phytase in the diet. DOI: http://dx.doi.org/10.3329/bjas.v43i1.19385 Bang. J. Anim. Sci. 2014. 43 (1): 52-55